Competition Laws And Digital Markets In Developing Countries - El Bazzim, Rachid (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
Developing countries have responded to the extremely rapid growth of the digital economy and new associated model platforms by introducing measures to regulate them. However, these measures most often appear to already be outdated. Simultaneously, competition law seems unable to control these evolutions, in part because of the tools which are inapplicable to this new economy. Competition law has demonstrated a flexibility allowing it to adapt to different sectors. Far from pushing for disguised or authoritarian interventionism, it supports changing the culture, tools and procedures used and moving towards regional cooperation to better understand the digital economy. There is no doubt that speed of execution is a key element in determining its effectiveness. Hence, this contribution also examines using provisional measures as procedural tools. Developing countries must pursue developments that will profoundly change their societies and foundational legal standards. The increasing emergence of connected objects on the market will create or modify many interdependent markets, which may in turn highlight new issues. Thus, it will be necessary for these countries to know how to address the problems that will arise, including the question of the local economy and small-to-medium enterprises (SMEs). Competition law and the competition authorities that practice it must evolve to accompany changes and ensure the proper function of the economies of developing countries.